VD_FINDINFO HC / 2015 / 247 vom 19. März 2015 - VD Tribunal cantonal (2015)
DÉCISION D'IRRECEVABILITÉ, EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, CONCLUSIONS | 337 al. 1 CPC (CH), 337 CPC (CH), 341 al. 3 CPC (CH), 341 CPC (CH)